2007
DOI: 10.1111/j.1440-1835.2007.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Cochlodinium fulvescens sp. nov. (Gymnodiniales, Dinophyceae), a new chain‐forming unarmored dinoflagellate from Asian coasts

Abstract: Cellular morphology and the phylogenetic position of a new unarmored photosynthetic dinoflagellate Cochlodinium fulvescens Iwataki, Kawami et Matsuoka sp. nov. were examined by light microscopy and molecular phylogenetic analyses based on partial large subunit ribosomal DNA (LSU rDNA) and small subunit ribosomal DNA (SSU rDNA) sequences. The cells of C. fulvescens closely resemble C. polykrikoides, one of the most harmful red tide forming dinoflagellates, due to it possessing a cingulum encircling the cell app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 18 publications
6
59
0
Order By: Relevance
“…2K-L) is similar to C. fulvescens as both species form cell chains and have a nucleus and an eyespot located in the anterior dorsal part of the cell (Iwataki et al 2007. The presence of an eyespot was demonstrated for C. polykrikoides by TEM in Iwataki et al (2010).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…2K-L) is similar to C. fulvescens as both species form cell chains and have a nucleus and an eyespot located in the anterior dorsal part of the cell (Iwataki et al 2007. The presence of an eyespot was demonstrated for C. polykrikoides by TEM in Iwataki et al (2010).…”
Section: Resultsmentioning
confidence: 82%
“…Cochlodinium fulvescens is a bloom-forming dinoflagellate first found in Tachibana Bay (west Japan), Hurun Bay (South Sumatra), Indonesia (Iwataki et al 2007), British Columbia , California , Curtiss et al 2008, Kudela & Gobler 2012 (Figs. 2K-L) is similar to C. fulvescens as both species form cell chains and have a nucleus and an eyespot located in the anterior dorsal part of the cell (Iwataki et al 2007.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no Cochlodinium bloom was ever observed in Indonesia. Previous research had identified C. fulvescens phytoplankton in December 2003 in Lampung Hurun Bay which was an area for mariculture in floating net cages; however, this species was found not to induce red tides as that occurred in 2012 [6].…”
Section: Introductionmentioning
confidence: 90%
“…Figure 3 Morphological comparison among Cochlodinium sp. occurred in Lampung Bay, C. fulvescens [6,17] and C. polykrikoides [6] is described below (table 3). Furthermore, it is evident that Choclodinium sp.…”
Section: Composition and Abundance Of Phytoplanktonmentioning
confidence: 99%